Caracterización de personas lesionadas en accidentes de tránsito ocurridos en Medellín y atendidas en un hospital de tercer nivel, 1999-2008 (2010)
ABSTRACT: Traffic accidents are a social and public health problem all over the world that output injured people which become susceptible to suffering disability, psychological damage or death representing a high economic cost. There are just a few researches about morbidity and severity of injured people in Medellín. Objective: to describe the characteristics of people, time, place and vehicle in traffic accidents in Medellín that were assisted in a general hospital between 1999 and 2008. Methodology: retrospective descriptive study with data taken from the unique claim form managed by the Mandatory Insurance for Traffic Accidents (soat) applied to 29.676 people injured. Results: 34,3% was admitted in the afternoon, 52,0% in weekends and holidays and 67,0% lived in Medellín. 50,3% was admitted in the hospital in the first hour after the accident and 78,1% were discharged the same day. More than 50% were young men with ages 20-39 years. The most affected anatomical areas were the head, face or neck (25,8%) and lower extremities (25,2%). Motorcyclists were 79,6%, and 43,2% suffered injuries in collisions. 54,7% had minor injuries. Global mortality was 1,5%. Discussion: Knowledge about the characteristics of people who are seen in emergency departments of these cities, including Medellín, is small.